Motivasi Belajar Siswa Dalam Kegiatan Ekstrakurikuler Sepak Bola Dengan Hasil Belajar PJOK Siswa - I Gede Windu Yasa; I Wayan Artanayasa; Kadek Yogi Parta Lesmana (Jurnal Sporta Saintika, 2025)
The study aims to determine and test the relationship between students' learning motivation in extracurricular soccer activities with learning outcomes in Physical Education, Sports, and Health (PJOK) subjects. This research was conducted at SD Negeri 3 Ulakan to determine the relationship between students' learning motivation in participating in extracurricular soccer activities and their PJOK learning outcomes, with the aim of helping students develop their learning outcomes and add to their abilities, both academic and non-academic. The population of this study was all fifth-grade students of SD Negeri 3 Ulakan Karangasem, totaling 26 students. The study is a quantitative descriptive study included in correlational research. The instruments used were the learning motivation scale and PJOK learning outcomes. Data analysis in this study used SPSS 23 with bivariate techniques. The results of the study showed an r value of 0.719 and Sig. (2-tailed) 0.000 <0.005. Based on the results of the study, it can be concluded that there is a significant relationship between learning motivation and PJOK learning outcomes.